Application of N parallel-connected SiC MOSFETs to solid-state circuit breakers based on UIS tests. (November 2022) - Lou, Zaiqi; Saito, Wataru; Nishizawa, Shin-ichi
Abstract: N parallel-connected SiC MOSFETs were investigated to apply to solid-state circuit breakers (SSCB), and it is an extension of a method that was proved valid by experiment of two parallel-connected SiC MOSFETs. The unclamped inductive switching (UIS) test was considered as the emergency interruption of SSCBs in this research. Because of the variations of breakdown voltage among SiC MOSFETs, the current flowing through devices is imbalanced during emergency interruption of SSCBs, which can drive some of the devices into thermal destruction prematurely. There are many compound cases for several SiC MOFETs with a certain maximum breakdown voltage variation. And the worst case, where the breakdown voltage of one device is assumed as the lowest, whereas the other devices have the same breakdown voltage, was extracted from the calculated results of four parallel-connected situation. In the worst case, it was found that the relation of breakdown voltage variations and current capacity is linear. Moreover, the distributions of breakdown voltage were taken as normal distributions. Using the worst case and distributions, a linear relation of breakdown voltage distributions and rated current of an SSCB could be concluded as a function of paralleled-connected numbers (N). Utilizing the function, the necessary breakdown voltage distributions and N of SiC MOSFETs can be evaluated for SSCBs meeting a certain yield ratio and current. Highlights: Design method of solid-state circuit breakers with parallel-connected SiC MOSFET Clarifying acceptable breakdown voltage between parallel-connected SiC MOSFET in the unclamped inductive tests Taking the breakdown voltage distribution as a normal distribution to calculate the yield of solid-state circuit breakers